2022
DOI: 10.12701/jyms.2021.01683
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic neuromodulation with gamma oscillation as a new strategy for Alzheimer disease: a narrative review

Abstract: Alzheimer disease (AD), age-dependent dementia characterized by irreversible and progressive loss of memory and cognition, shows an approximately 11.3% prevalence in patients aged 65 years and older in the United States [1]. The prevalence of dementia was reported to be 10.2% in the Republic of Korea, of which approximately 74.5% were diagnosed with AD [2]. Both reports showed that the incidence of AD increases with age and that the prevalence of AD is expected to increase until 2050. The cause of AD is not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Studies in human aging have only found positive associations between local gamma power and β-amyloid burden in AD patients rather than gamma widespread synchrony (see Babiloni et al, 2021 for a review). Studies in human aging are increasingly carried out to clarify the association between gamma-band and βamyloid burden as gamma sensory stimulation is considered as a potential therapeutic strategy in AD (see Ko et al, 2022 for a review). We here provide arguments to consider gamma fluctuations as a marker of the progression of β-amyloid deposition.…”
Section: Distinct Theta and Gamma Association With Ad Pathological Ma...mentioning
confidence: 99%
“…Studies in human aging have only found positive associations between local gamma power and β-amyloid burden in AD patients rather than gamma widespread synchrony (see Babiloni et al, 2021 for a review). Studies in human aging are increasingly carried out to clarify the association between gamma-band and βamyloid burden as gamma sensory stimulation is considered as a potential therapeutic strategy in AD (see Ko et al, 2022 for a review). We here provide arguments to consider gamma fluctuations as a marker of the progression of β-amyloid deposition.…”
Section: Distinct Theta and Gamma Association With Ad Pathological Ma...mentioning
confidence: 99%
“…The existing therapeutic landscape for AD emphasizes the pressing need for innovative approaches that target the root causes of the disease [5]. Aging-associated neurodegenerative diseases, characterized by progressive neuronal death and synapse loss in the human brain, are rapidly growing and affecting millions of people globally [6]. AD is clinically manifested by progressive impairment in cognition, learning ability, memory function, and executive reasoning [7].…”
Section: Introductionmentioning
confidence: 99%
“…By stimulating with light, this method provides high-spatiotemporal and high-specificity resolutions, in contrast to conventional pharmacological or electrical stimulation [ 18 , 19 ]. Optogenetics provides a route to study synaptic circuits [ 20 ] and underlying movement diseases [ 21 , 22 ] and has become an effective technology to revolutionize brain research for the therapy of vision [ 23 , 24 , 25 ], cardiovascular [ 26 ], and neurodegenerative disorders [ 27 , 28 ]. It has also been extended to other biomedical fields [ 29 , 30 ].…”
mentioning
confidence: 99%